Amplifying Local Leadership: A Twitter Analysis of Indonesian Responses to the COVID-19 Pandemic - Kusumasari, Bevaola; Fauzi, Fadhli Zul; Santoso, Anang Dwi (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2023)
Social media has altered emergency communication between local governments and citizens. Studies on social media and natural disasters are expanding. Few studies have explored the crisis of social media use among local government officials. This study investigated how Indonesian leaders use social media. It used data scraping techniques with the Twitter API and the http://tweepy.readthedocs.io/en/v3.5.0/api.html#tweepy-api-twitter-api-wrapper library to collect tweets from each governor's account in Bahasa, Indonesia, between January 1, 2020, and December 31, 2020. The collected data were stored in a MySQL database to facilitate manual analysis and converted to text format. The data were manually labeled using a three-step coding procedure and assigned to categories to identify social media trends among local government leaders during the COVID-19 pandemic. This study examines the government response effectiveness concept, which depends on the timeliness and breadth of official engagement and how communities receive, perceive, and respond to information provided by governments and other agencies. Four leaders demonstrated compassion, care, and self-assurance throughout the pandemic. Leaders must have two-way communication. A recent study investigated the Twitter links between local leaders and pandemic victims. This study supports the notion that social media use by government officials during epidemics influences community perceptions of risk and trust, thereby influencing policy decisions. These findings have policy ramifications, notably for establishing social media restrictions for local government leaders during future health emergencies.